Is excision repair cross-complementation Group1 expression a biological marker in nasopharynx carcinoma - Aksoy, Asude; Elkiran, Emin Tamer; Harputluoglu, Hakan; Dagli, Adile Ferda; Isikdogan, Abdurrahman; Urakci, Zuhat (Wolters Kluwer Medknow Publications, 2019)
Objective: To determine the prognostic value of excision repairs cross-complementation group1 (ERCC1) gene in cases with nasopharyngeal carcinoma (NPC) treated with platinum-containing chemotherapy (PCT). Subjects and Methods: The present study was included 33 cases in local advanced stage with NPC. ERCC1 expression was evaluated by using immunohistochemical staining in biopsy specimens. We evaluated the relationship between the degree of ERCC1 expression and clinicopathological features, response to therapy, survival rates in cases with NPC, retrospectively. Results: ERCC1 expression was not observed in 5 (15.15%) of all cases. Thirteen (39.9%) cases weakly positive (+1, +2) and 15 (45.5%) cases of all them were rather strongly positive (+3). There was no statistically significant difference between the degree of ERCC1 expression and clinicopathological features, response to treatment, survival rates (P 0.05) in cases with NPC. Conclusions: ERCC1 expression has no predictive value for survival in cases locally advanced stage with NPC. Evaluation of ERCC1 expression is not appropriate with a biomarker to detect cases who can benefit from PCT in NPC.
Keywords: Excision repair cross-complementation group1; nasopharyngeal carcinoma; platinum resistance; survival